Pencegahan pencemaran lingkungan berbasis komunitas RT sebagai implementasi prinsip pencegahan dalam hukum lingkungan - Taufiq Supriadi; Reinhart Christian; Fabrian Iman Laksmono Simorangkir; Rd. Shabrina Azwa Aqila (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Environmental pollution problems in densely populated residential areas arise from inadequate and inadequate management of household waste. There are growing demands for environmental pollution prevention efforts involving the active participation of local residents. This study aims to analyze the trend of community-based environmental pollution prevention efforts within the Neighborhood Association (RT) using qualitative methods with empirical data supported by field observations and interviews in the Indonesian Planet Crisis Prevention (PKPI) area of ​​RT 08 RW 04, Malaka Jaya Village, Duren Sawit District, East Jakarta. The results show that residents' practices and efforts in environmental management, including household waste management, composting and biopores, catfish cultivation in ditches and community nutrient ponds, and the use of solar energy, demonstrate the implementation of environmental impact prevention principles by local residents. However, the desire to implement these prevention practices is closely related to the level of community participation and institutional support. This study concludes that community-based environmental pollution prevention demonstrates the implementation of the prevention principle in environmental law in densely populated residential areas.